ANALISIS CASH HOLDING BERBASIS KEKUATAN KAS DAN MODAL KERJA BERSIH - Anggita Windi Astuti; Gendro Wiyono; Mujino Mujino (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2019)
This study aims to determine the effect of cash flow, cash conversion cycle, and networking capital on cash holding both partially and simultaneously. The population used in this study were 21 food and beverages sub-sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period. The sample used uses the purposive sampling method. The data analysis technique used is the method of multiple regression analysis with a significant level and hypothesis testing using the F test and t-test. From the results of the study, it can be concluded that cash flow has no effect on cash holding. Cash conversion cycle variable has a significant negative effect on cash holding. The variable net working capital has a significant positive effect on cash holding. While simultaneous variables of cash flow, cash conversion cycle, and networking capital affect the cash holding of food and beverages sub-sector companies listed on the Indonesia Stock Exchange in the 2014-2018 period.